2008
DOI: 10.1523/jneurosci.1424-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Programming of Offspring Emotionality after Stress Early in Pregnancy

Abstract: Prenatal stress is associated with an increased vulnerability to neurodevelopmental disorders, including autism and schizophrenia. To determine the critical time window when fetal antecedents may induce a disease predisposition, we examined behavioral responses in offspring exposed to stress during early, mid, and late gestation. We found that male offspring exposed to stress early in gestation displayed maladaptive behavioral stress responsivity, anhedonia, and an increased sensitivity to selective serotonin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
769
11
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 907 publications
(826 citation statements)
references
References 48 publications
42
769
11
4
Order By: Relevance
“…Many of the programmatic changes produced in our EPS mouse model are endophenotypes of neurodevelopmental disorders, including stress dysregulation, cognitive dysfunction, and hypothalamic dysregulation of growth and development (4,(6)(7)(8)(9)(10). These outcomes support the critical communication from the placenta to the fetus related to the bioenergetic or metabolic environment that then programs the hypothalamus, the brain's endocrine and metabolic regulatory center.…”
mentioning
confidence: 84%
“…Many of the programmatic changes produced in our EPS mouse model are endophenotypes of neurodevelopmental disorders, including stress dysregulation, cognitive dysfunction, and hypothalamic dysregulation of growth and development (4,(6)(7)(8)(9)(10). These outcomes support the critical communication from the placenta to the fetus related to the bioenergetic or metabolic environment that then programs the hypothalamus, the brain's endocrine and metabolic regulatory center.…”
mentioning
confidence: 84%
“…For instance, in neuropsychiatric diseases such as autism, schizophrenia, or depression, although men and women may be given a similar diagnosis, there exist significant sex differences in overall rates, timing of onset, symptom presentation, and treatment efficacy (Heim and Nemeroff, 1999;Heim and Nemeroff, 2001;Sanchez et al, 2001;Goldstein et al, 2002;Heim et al, 2004;Bale, 2006;Brown and Susser, 2008;Bale, 2009;Brown et al, 2009;Heim et al, 2009;Bale et al, 2010;Heim et al, 2010;Brown, 2012;Davis and Pfaff, 2014;Goldstein et al, 2014). Further, mechanistic animal studies modeling endophenotypes of these disorders have demonstrated robust sex differences in the timing of susceptibility to insults to the developing brain where males appear more vulnerable prenatally and females postnatally (Mueller and Bale, 2006;Mueller and Bale, 2007;Ivy et al, 2008;Kapoor et al, 2008;Mueller and Bale, 2008;Kapoor et al, 2009;Ivy et al, 2010;Hsiao and Patterson, 2012). Therefore, although a male and a female may both be diagnosed with the same disease, for instance autism, the means by which that disease was programmed and presented may be sex-specific.…”
Section: Knowledge Gained By Including Sabv In Studies Of Neurodevelomentioning
confidence: 99%
“…Animal studies have shown that maternal exposure to drugs (10), stress (11), and endocrine disruptors (12) during pregnancy can alter epigenetic gene programming in the brain and contribute to neurodevelopmental deficits in offspring. Several studies have linked gestational (13,14) or neonatal (15,16) BPA exposure to long-lasting changes in DNA methylation and altered gene expression in nonneuronal tissues.…”
mentioning
confidence: 99%